DIFFERENCES AND SIMILARITIES IN FREQUENCY AND OCCURRENCE OF CERTAIN EUPHEMISTIC EXPRESSIONS RELATED TO OBESITY IN DIFFERENT GENRES OF THE ENGLISH-SPEAKING WRITTEN MEDIA AND AT DIFFERENT TIME PERIODS - M. Laskova; K. Kotikova (Гуманитарные и юридические исследования)
Euphemisms are the main social lingua non franca. They allow speakers to mitigate the meaning of what has been said or what is going to be said if the words are offensive, indecent or unpleasant. Their analysis allows understanding what is going on in the language, minds and culture of people. The subjects that we tend to use euphemisms for change along with our social attitudes. Nowadays, one of the most vital subjects is a political correctness movement which criticizes the usage of words that may offend certain group members, that is why euphemisms are used instead. The word "obesity", like many medical terms, came into the vernacular vocabulary with the attached stigma. As a result, the association influenced people to use the words "obese" and "obesity" with care and replace them with euphemisms. A number of studies of euphemisms were conducted within linguistics; a number of studies in English were carried out in order to identify preferred terms and communication styles of speaking with the patients about obesity, fat stigma and ways of discussing it in the modern society. However, little research has been made in order to scrutinize the occurrence and periodicity of the related to obesity euphemisms usage in various media. Given the scarcity of such analysis, this study aims to analyze the occurrence and periodicity of the usage of related to obesity euphemisms in the different media and in different time periods. For this purpose, we collected data on euphemisms and analyzed it via language corporain the iWeb corpus (contains 14 billion words in 22 million web pages) and the Corpus of Contemporary American English (consists of more than 560 million words in 220,225 texts). Then, we presented the overall occurrences of euphemisms followed by their percentages in different genres and a more detailed analysis of certain euphemisms. Due to a limited number of analyzed euphemisms and mainly descriptive nature of this study, it is not fully conclusive, but it might be used for a future research analyzing larger expressions for a more complex analysis.